Public and Stakeholder Engagement in Developing Human Heritable Genome Editing Policies: What Does it Mean and What Should it Mean? - Iltis, Ana S.; Hoover, Sarah; Matthews, Kirstin R. W. (Frontiers in Political Science, 2021)
As scientific research pushes the boundaries of knowledge, new discoveries and technologies often raise ethical and social questions. Public responses vary from surprise, to unrealistic optimism about imminent new treatments, confusion, and absolute opposition. Regardless of the intent, the use of a precise gene editing tool on human embryos, such as CRISPR-Cas9, is an example of such a controversial emerging technology. Substantive disagreement about the appropriate research pathways and permissible clinical applications is to be expected. Many ethical concerns, especially related to genetic manipulation of human embryos, are rooted in deeply held moral, religious, or ideological beliefs that science alone cannot address. Today, more scientists and scientific societies as well as policy makers are calling for public and stakeholder engagement in developing guidelines and policies governing scientific practice. We conducted a critical interpretive review of the literature on public and stakeholder engagement in science policy development regarding emerging technologies to determine the ideals that should guide engagement efforts of entities developing recommendations or guidelines on policy for such technologies. We identify and describe five ideals. To illustrate possible applications of these ideals, we review the engagement efforts described in three reports on heritable human genome editing and assess those efforts in light of these ideals. Finally, we recommend possible avenues for engagement that would advance those goals.